Effect Domino Kebijakan Moneter The FRS As Terhadap Perekonomian Indonesia - Tia Ichwani; Rika Kaniati; Hikmatul Husna (JRB-Jurnal Riset Bisnis, 2018)
This study aims to determine the implementation of monetary policy conducted by The US Federal Reserve on the movement of interest rates of Bank Indonesia (BI 7 Days Repo), Rupiah exchange rate against US Dollar, Indonesia inflation rate and export value of Indonesia.The research method used is quantitative descriptive method with the aim to create a systematic, factual and accrual picture of the facts of reality in that year. The data used are secondary data, which are historical data on FFR, inflation, monetary policy and rupiah exchange rate.From the results of the analysis and discussion, it can be concluded that the monetary policy undertaken by the United States Government in dealing with its economic problems in 2017 - 2018 is to raise the federal rate (FFR) periodically and indirectly, this affects the value of Indonesian exports.